Composition analysis and mechanism of Guizhi Fuling capsule in anti-cisplatin-resistant ovarian cancer - Lei Dou; Yan Yan; Enting Lu; Fangmei Li; Dongli Tian; Lei Deng; Xue Zhang; Rongjin Zhang; Yin Li; Yi Zhang; Ye Sun (Translational Oncology)
Objective: Cisplatin is the main chemotherapy drug for advanced ovarian cancer, but drug resistance often occurs. The aim of this study is to explore the molecular mechanism by which Guizhi Fuling capsule inhibits cisplatin resistance in ovarian cancer. Methods: First, differences in cisplatin resistance, PA2G4 gene expression, migration, and invasion in A2780 cells and A2780/DDP cells were analyzed by qRT-PCR, scratch assay, transwell, immunofluorescence, and western blotting. Then, LC-MS/MS analysis of GFC chemical composition. qRT-PCR, scratch tests, transwell, pseudopodium formation, immunofluorescence, and western blotting were used to explore the mechanism by which GFC inhibited A2780/DDP cell migration and invasion. Finally, the anti-tumor efficacy of GFC was verified by in vivo experiments. Results: A2780/DDP cells had a greater ability to migrate and invade compared to their parents. Cell viability experiments showed that the migration and invasion ability of A278/DDP cells were significantly inhibited with the increase of GFC concentration. qRT-PCR results showed that compared with the blank control group, cisplatin group and GFC group, the transcription level of PA2G4 gene in the combination treatment group was significantly reduced. We also found that GFC combined with cisplatin inhibited the PI3K/AKT/GSK-3β signaling pathway by targeting PA2G4 gene expression, inhibited the epithelial-mesenchymal transition signaling pathway, decreased cell adhesion and inhibited the formation of cell pseudopodias. Conclusion: GFC combined with cisplatin can target PA2G4 gene to regulate PI3K/AKT/GSK-3β Signaling pathway, inhibiting the invasion and migration of cisplatin resistant A2780/DDP cells in ovarian cancer.